Long‐Term Temperature Impacts of the Hunga Volcanic Eruption in the Stratosphere and Above - William J. Randel; Xinyue Wang; Jon Starr; Rolando R. Garcia; Douglas Kinnison (Geophysical Research Letters)
Abstract Global average upper atmosphere temperature changes linked with the Hunga volcanic eruption (January 2022) are analyzed based on satellite measurements and compared with chemistry‐climate model simulations. Results show stratospheric cooling of −0.5 to −1.0 K in the middle and upper stratosphere during 2022 through middle 2023, followed by stronger cooling (−1.0 to −2.0 K) in the mesosphere after middle 2023. The cooling patterns follow the upward propagating water vapor (H2O) anomalies from Hunga, and similar behavior is found between observations and model simulations. While the stratospheric cooling is mainly due to radiative cooling from enhanced H2O, the mesospheric temperature changes result from ozone losses in the mesosphere, which are in‐turn driven by HOx radicals from Hunga H2O. Comparisons with the multi‐decade climate record show that Hunga impacts on stratospheric temperatures have similar magnitude, but opposite sign, to temperature effects from the large El Chichón (1982) and Pinatubo (1991) volcanic eruptions.